Characterization of a monoclonal anti-idiotype antibody to human anti-factor VIII antibodies. - Lubahn, B C (1990)
Approximately 15% of individuals with hemophilia A develop antibodies (inhibitors) to therapeutically infused factor VIII that interfere with F.VIII coagulant activity. By using isoelectric focusing and immunospecific detection of anti-factor VIII antibodies, inhibitor plasma showed varied patterns of reactivity characteristic of a polyclonal response. Inhibitor plasma from patient Bt was observed to have an isolated banding pattern, or spectrotype, at pI 8.4 (SP8.4) distinct from his remaining anti-factor VIII antibodies. SP8.4 antibodies from this patient were partially purified and used to prepare monoclonal anti-idiotype antibodies. Monoclonal antibody Mab20-2H was found to detect a spectrotype in isoelectric-focused Bt plasma identical to SP8.4 and to bind anti-factor VIII antibodies. Furthermore, Mab20-2H binding could inhibit the binding of these anti-factor VIII antibodies to antigen, indicating that Mab20-2H recognizes an idiotope associated with antigen binding. Mab20-2H was also found to recognize antibodies from another inhibitor patient. This and other anti-idiotype reagents will be useful for defining genetic factors involved in the human immune response to factor VIII and in designing approaches to prevent or ameliorate this response.